Transformasi perpustakaan di era digital native - Vitriana, Novita (Librarium: Library and Information Science Journal, 2024)
Introduction. Digital libraries, as a form of library transformation, are tied to their role as educational centers for all communities. Libraries must maximize their role for millennial readers in this digital native era. This research aims to find out how library transformation contributes to the needs of librarians in the digital native era and also the librarian competencies that librarians must have. This is done because digital natives prefer the internet as the primary information reference source. Digital native is a description of the current generation who are used to fast responses, don't like to wait, and new technology makes them addictive. Research methods. This research is library research with a qualitative approach to obtain detailed information by exploring the substance of information or empirical data obtained from books, results of scientific or formal research reports, or other literature. Data Analysis. Data analysis is done by collecting articles and readings about library transformation and digital natives, which are then classified, analyzed, and interpreted to reach conclusions. Results and Discussion. This research concludes that libraries are obliged to realize data technology as an opportunity to develop rather than view it as an obstacle that will threaten the library's existence. Librarians must be ready and proactive about data technology, information and science advances. Librarians must be active, creative, innovative, and always follow advances in data technology. Conclusions and recommendations. Libraries must change service patterns and improve all matters related to library facilities. Keywords: Transformation, Library, Digital Native ================ Pendahuluan. Perpustakaan digital sebagai salah satu wujud transformasi perpustakaan terikat dengan perannya sebagai pusat pendidikan semua masyarakat. Perpustakaan harus mampu memaksimalkan peranannya buat pemustaka milenial di masa digital native ini. Tujuan penelitian ini adalah untuk mengetahui bagaimana transformasi perpustakaan berkontribusi dengan kebutuhan pemustaka di era digital native dan juga kompetensi kepustakawanan yang harus dimiliki oleh pustakawannya. Hal tersebut dilakukan karena para digital native lebih memilih internet sebagai sumber utama rujukan informasi. Digital native merupakan gambaran generasi saat ini yang terbiasa dengan respon cepat, tidak suka menunggu dan teknologi baru membuatnya candu. Metode penelitian. Riset ini merupakan riset kepustakaan dengan pendekatan kualitatif guna memperoleh informasi yang detail, dengan mengeksplorasi substansi dari informasi ataupun data empirik yang diperoleh dari buku, hasil laporan riset ilmiah ataupun formal maupun dari literatur yang lain. Data Analisis. Analisis data dengan mengumpulkan artikel dan bacaan tentang transformasi perpustakaan dan digital native yang kemudian diklasifikasi, dianalisa dan diinterpretasi sampai mendapat kesimpulan. Hasil dan Pembahasan. Hasil riset tersebut menyimpulkan bahwa perpustakaan wajib merealisasikan teknologi data sebagai kesempatan untuk berkembang serta tidak menganggapnya sebagai hambatan yang akan mengancam eksistensi perpustakaan. Bagi pustakawan harus siap dan juga proaktif terhadap kemajuan teknologi data, informasi dan ilmu pengetahuan. Pustakawan harus aktif, kreatif, inovatif, serta selalu mengikuti kemajuan teknologi data tersebut. Kesimpulan dan Saran. Perpustakaan harus mengubah pola layanan dan membenahi semua hal yang berhubungan dengan fasilitas perpustakaan.